Improving the adaptability of an active power filter using linearization feedback input-output sliding mode - Huynh, Leminh Thien; Ho, Van-Cuu; Tran, Thanh-Vu (International Journal of Applied Power Engineering (IJAPE), 2025)
As more and more non-linear loads are used in industrial applications, power quality problems become more serious. To address this challenge, a robust nonlinear control strategy is introduced using an active power filter (APF) to enhance the power quality of the three-phase neutral voltage. The system employs a control algorithm tailored for a three-phase split-capacitor inverter, which eliminates high-order harmonics through a voltage source inverter (VSI) equipped with an LCL filter. The grid-side components of the LCL filter are incorporated into a sliding mode control framework to minimize oscillations while maintaining performance. Additionally, the d-q-0 transformation within the synchronous reference frame is applied to effectively manage the second harmonic component. In addition, the linear feedback input-output sliding mode facilitates the control system. This system can help decrease total harmonic distortion (THD) to meet IEEE-519 standards. This method demonstrates its effectiveness through simulation results, reducing THD to less than 5% and defeating previous methods despite still using simple algorithms.